Нетопырь средиземноморский (Pipistrellus kuhli Natterer, 1819) в Средней Азии - Стрелков, П.П. (Вестник зоологии, 1973)
Many colonies of Pipistrellus kuhli N a t t e r e r were at first found in south-western Turkmenia in the lower reaches of Atrek and Sumbar. It is supposed that in other retions of the Soviet Middle Asia finding of this species is hardly probable, as in the eastern part of the areal the north boundary of the species distribution deviates to the south rounding the boundary mountain ridges. Animals from south-western Turkmenia should be attributed to the subspecies P. kuhli lepidis.